Efficiency of NO donors in substituting impaired endogenous NO production: a functional and morphological study - Gerová, M; Kristek, F (Physiological research, 2001)
Two exogenous NO donors were used to act as substitutes for impaired endogenous nitric oxide (NO) production due to inhibition of NO synthase in rats. Six weeks' lasting inhibition of NO synthase by NG-nitro-L-arginine methyl ester (L-NAME) induced stabilized hypertension. Simultaneously administered isosorbide-5-mononitrate did not prevent the development of hypertension. Molsidomine, administered concomitantly with L-NAME, significantly attenuated the BP increase. However, BP was still found to be moderately increased compared to the initial values. Remarkable alterations in the geometry of the aorta, carotid and coronary artery found in NO-deficient hypertension were prevented in rats administered L-NAME plus molsidomine at the same time. In spite of 6 weeks' lasting inhibition of NOS, the NOS activators acetylcholine and bradykinin induced BP decrease; the maximum hypotensive value did not differ from the values recorded in the controls or in animals treated with L-NAME plus molsidomine. Notably enough, the hypotension was similar to that found in rats administered L-NAME alone for six weeks. After NO synthase inhibition, Isosorbide-5-mononitrate does not substitute and molsidomine substitute only partially the impaired endogenous NO production.
Keywords: bradykinin; Nitric Oxide Synthase; Nitric Oxide Donors; Rats; isosorbiddinitrát; donory oxidu dusnatého; Acetylcholine; krevní tlak; molsidomin; Bradykinin; NG-nitroargininmethylester; Hypertension; Isosorbide Dinitrate; acetylcholin; Rats, Wistar; mužské pohlaví; krysa rodu Rattus; Molsidomine; Enzyme Activation; synthasa oxidu dusnatého; zvířata; Blood Pressure; oxid dusnatý; vazodilatancia; Nitric Oxide; Vasodilator Agents; hypertenze; aktivace enzymů; potkani Wistar; Enzyme Inhibitors; NG-Nitroarginine Methyl Ester; Male; inhibitory enzymů; Animals